1987
DOI: 10.1111/j.1365-2125.1987.tb03145.x
|View full text |Cite
|
Sign up to set email alerts
|

Placebo does not lower ambulatory blood pressure.

Abstract: The effects of 4 weeks of placebo on clinic and on ambulatory blood pressure, measured non‐invasively using the Remler M 2000 portometer, were studied in 46 hypertensive patients who were included in three consecutive double‐blind randomized placebo‐controlled trials with antihypertensive drugs. Placebo significantly reduced clinic blood pressure, but had no significant effect on ambulatory blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…It has been shown that 24-h average BP is not reduced by placebo. 3,22,23 A small decrease in BP, however, may be observed during the first 2-6 h of ambulatory monitoring in placebo-treated groups. 21,23,24 This effect seems inconsistent and, in contrast to the treatment-induced effect, is not normally distributed.…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that 24-h average BP is not reduced by placebo. 3,22,23 A small decrease in BP, however, may be observed during the first 2-6 h of ambulatory monitoring in placebo-treated groups. 21,23,24 This effect seems inconsistent and, in contrast to the treatment-induced effect, is not normally distributed.…”
Section: Discussionmentioning
confidence: 95%
“…It has been claimed that an advantage of indirect ambulatory blood pressure measurement is the absence of a placebo effect. 14,15 Continuous ambulatory blood pressure monitoring is considered to improve the reproducibility of blood pressure measurement which can improve the exactness of clinical trials. It is also possible to reduce the number of subjects required.…”
Section: Discussionmentioning
confidence: 99%
“…When a monitor is first applied to a patient the values in the first 60-90 min are high 13,14 and closer to the value measured by clinical sphygmomanometry ( Table 2). Whether this occurs with subsequent ABPM has not been rigorously documented but in our experience it does, though Despite initial statements to the contrary [14][15][16] there is a significant placebo effect with 24-h ABPM. 17,18 Though relatively small in an absolute sense (systolic 2 mm Hg, diastolic 1.5 mm Hg), in the context of a total change of 8-10 mm Hg with monotherapy the effect may have an important impact on the T:P ratio.…”
Section: Twenty-four Hour Ambulatory Bp Monitoring (Abpm)mentioning
confidence: 83%